Upaya Peningkatan Motivasi Ibu Hamil dalam Rangka Mempersiapkan ASI Eksklusif melalui Edukasi menggunakan Media Video Animasi di Wilayah Kerja Puskemas Karanggede - Winarsih, Winarsih; Rismawati, Rismawati; Dwihestie, Luluk Khusnul (Universitas Pahlawan Tuanku Tambusai, 2026)
Reason for Choosing Topic: Motivation for breastfeeding is defined as an attitude of creating a situation that stimulates the mother's enthusiasm to breastfeed her baby. The results of interviews with the head of the Karanggede Community Health Center and the KIA Coordinator Midwife on May 2, 2025 through the 2024 mini workshop data obtained the results that the coverage of exclusive breastfeeding was 112 (72%) of 154 babies. This figure is still far from the target of 80%. Objective: to increase the motivation of pregnant women through animated video media In the Framework of Preparing Exclusive Breastfeeding Through Education Using Animated Video Media. Community service method: The method of implementing PKM with a counseling model, lectures and questions and answers with animated video media. Summary of Results: PKM activities went smoothly, the target was pregnant women from TM 1 to TM III. The activity was held on Thursday, August 7, 2025 starting at 09.00 to 12.00 WIB. The participants who attended were 29 pregnant women in the Karanggede Community Health Center work area. The results of the PKM activity increased the motivation of mothers to intend to provide breast milk.